PEMECAHAN MASALAH KOMPETISI MATEMATIKA BAGI GURU SEKOLAH DASAR TAHAP I - Rudi Santoso Yohanes; Ana Easti Rahayu Maya Sari (Institute of Research and Community Outreach - Petra Christian University, 2021)
The rapid development of science and technology ushers people into the era of global competition in various fields of science, one of which is mathematics. The national mathematics competition at sd/mi level that has been pioneered in 2003 is one of the strategic containers to realize the educational paradigm. But even so, not all teachers are able to follow the wishes of science and technology. The current condition also requires teachers to be able to follow the development of science and technology in training and accompanying students in self-learning from their own homes. Before this condition teachers have also been subjected to demands to be able to train students to compete in academic fields such as mathematics. However, not all teachers are able to provide proper training to students as a form of preparation for them when they want to enter the competition. Math Competition Problem Solving Training activity is one form of activity that is expected to be a solution to the condition The training activity which was attended by 15 people consisting of 9 teachers, 1 lecturer, 1 civil servant, 1 housewife and 3 students received a positive response through questions and problem solving that had been given during the training, so it will be a consideration for the plan of implementation of similar activities next. Abstrak: Pesatnya perkembangan ilmu pengetahuan dan teknologi mengantarkan manusia ke era kompetisi global di berbagai bidang ilmu salah satunya adalah matematika. Kompetisi matematika nasional tingkat SD/MI yang telah dirintis tahun 2003 merupakan salah satu wadah yang strategis untuk merealisasi paradigma pendidikan. Namun meskipun demikian belum semua guru mampu untuk mengikuti perkembangan ilmu pengetahuan dan teknologi yang ada. Kondisi sekarang ini pun menuntut guru untuk bisa mengikuti perkembangan ilmu pengetahuan dan teknologi dalam melatih dan mendampingi siswa dalam belajar mandiri dari rumah mereka masing-masing. Sebelum kondisi ini guru pun juga sudah mendapatkan tuntutan untuk dapat melatih siswa agar dapat berkompetisi dibidang akademik seperti matematika. Meskipun demikian belum semua guru mampu untuk memberikan latihan yang tepat kepada siswa sebagai bentuk persiapan bagi mereka ketika hendak mengikuti kompetisi. Kegiatan Pelatihan Pemecahan Masalah Kompetisi Matematika merupakan salah satu bentuk kegiatan yang diharapkan mampu menjadi solusi terhadap kondisi tersebut. Kegiatan Pelatihan yang diikuti oleh 15 orang ini yang terdiri atas 9 orang guru, 1 dosen, 1 pegawai negeri sipil, 1 ibu rumah tangga dan 3 mahasiswa ini mendapatkan respon yang positif melalui pertanyaan dan penyelesaian soal yang telah diberikan selama pelatihan sehingga akan menjadi pertimbangan untuk rencana pelaksanaan kegiatan serupa berikutnya.